Overcoming dormancy and light quality in the germination of seeds of Leucaena leucocephala (Lam.) de Wit (Research, Society and Development, 2020)
This work aimed to study methods for overcoming the dormancy of Leucaena leucocephala seeds, besides evaluating their germination response in different light regimes. The treatments to evaluate dormancy were control, mechanical scarification with sandpaper, immersion in sulfuric acid, immersion in potassium nitrate concentrate, immersion in water at 80°C, incubation in a greenhouse at 70°C. To evaluate the quality of light, filters were tested in blue, red, green, absence of light and transparent (control). The experimental design was entirely randomized, with each treatment having four repetitions of 25 seeds each. The data were submitted to analysis of variance and the comparison between the means was made by Tukey's test at 5% probability. The treatment that best overcame the tegumentar dormancy of L. leucocephala seeds, with higher germination percentage and vigour was wood sandpaper nº180. For light quality the seeds of L. leucophala can be classified as photoblastic neutral, because the absence or presence of light did not interfere in their germination.